Research on the Application of Computer-aided Translation in the Field of Professional English. Issue 3 (October 2020) - Gao, Tingting; Wang, Xiaoyi
Abstract: With the economic globalization and the increasingly frequent economic and cultural cooperation between China and foreign countries, higher and faster requirements have been put forward for the translation work. The traditional translation mode has been unable to meet the current translation work. Then computer-aided translation has become the mainstream of today's translation work. This paper aims to study the application and research of computer translation in the field of professional English.